Effect of field margins on moths depends on species mobility: Field-based evidence for landscape-scale conservation - Merckx, T; Feber, R; Dulieu, R; Townsend, M; Parsons, MS; Bourn, N; Riordan, P; MacDonald, D (2009)
Agri-environment schemes (AES) are widely used policy instruments intended to combat widespread biodiversity declines across agricultural landscapes. Here, using a light trapping and mark-release-recapture study at a field-scale on nine common and widespread larger moth species, we investigate the effect of wide field margins (a popular current scheme option) and the presence of hedgerow trees (a potential scheme option in England) on moth abundance. Of these, we show that wide field margins positively affected abundances, although species did not all respond in the same way. We demonstrate that this variation can be attributed to species-specific mobility characteristics. Those species for which the effect of wide margins was strongest covered shorter distances, and were more frequently recaptured at their site of first capture. This demonstrates that the standard, field-scale uptake of AES may be effective only for less mobile species. We discuss that a landscape-scale approach, in contrast, could deliver significant biodiversity gains, as our results indicate that such an approach (perhaps delivered through targeting farmers to join AES) would be effective for the majority of wider countryside species, irrespective of their mobility level. © 2008 Elsevier B.V. All rights reserved.